Prevalence and predictors of resistant hypertension in a primary care setting: a cross-sectional study - Chia, Yook Chin; Ching, Siew Mooi (BioMed Central, 2014)
Background Patients with resistant hypertension are subjected to a higher risk of getting stroke, myocardial infarction, congestive heart failure and renal failure. However, the exact prevalence of resistant hypertension in treated hypertensive patients in Malaysia is not known. This paper examines the prevalence and determinants of resistant hypertension in a sample of hypertensive patients. Methods We examined the control of blood pressure in a randomly selected sample of patients with hypertension in a primary care clinic. Demographic data, blood pressure and anti-hypertensive drug use were captured from patient records at the end of 2007. Resistant hypertension is defined as failure to achieve target blood pressure of < 140/90 mmHg while on full doses of an appropriate three-drug regimen that includes a diuretic. Multivariate logistic regression was used for the analysis. Results A total of 1217 patients with hypertension were entered into the analysis. Mean age of the patients was 66.8 ± 9.7 years and 64.4% were female. More than half of the subjects (56.9%) had diabetes mellitus. Median BP was 130/80 mmHg. Overall prevalence of resistant hypertension was 8.8% (N = 107/1217). In multivariate logistic regression analysis, presence of chronic kidney disease is more likely to be associated with resistant hypertension (odds ratio [OR] 2.89, 95% confidence interval [CI] 1.56-5.35). On the other hand, increase per year of age is associated with lower odds of resistant hypertension in this population (OR 0.96, 95% CI 0.93-0.99). Conclusions Resistant hypertension is present in nearly one in ten hypertensive patients on treatment. Hypertensive patients who have underlying chronic kidney disease are associated with higher odds of having resistant hypertension. Hence, in managing patients with hypertension, primary care physicians should be more alert and identify patients with chronic kidney disease as such patients are more likely to develop resistant hypertension. By doing that, these patients can be treated more aggressively earlier in order to achieve blood pressure target and thus reduce cardiovascular events.